Establishing a national indicator-based surveillance system for hospital bed utilization by COVID-19 patients in the Philippines - Cabaro III, Bienvenido S; Dela Paz, Gabrielle Ann T; Dotingco, Jeffrey B; Almirol, Bernadette Joy Q; Borlongan, Gabriel R; Cebreros, Reena Ophelia D; Diangco, Patrick B; Quijalvo, Kenneth Pierre B; Tan, Joanne Pauline U; Tonato, Ramon Rafael D (Western Pacific Surveillance and Response, 2023)
In March 2020, the Philippine Department of Health (DOH) designed and rapidly implemented a national surveillance system for the utilization of hospital beds by patients with coronavirus disease (COVID-19) to produce complete and timely data for use by various levels of governance in response to the COVID-19 pandemic. The DOH launched the DOH DataCollect (DDC) Bed Tracker system, a web-based application that collects information from all 1906 public and private hospitals and infirmaries across the country using a modular data collection tool. Data on the maximum number of occupied COVID-19-designated beds (n = 28 261), hospital bed utilization rate (71.7%), and mechanical ventilator number (n = 1846) and utilization rate (58.5%) were recorded in September 2021 during the Delta surge of cases in the Philippines. Data on human resources, personal protective equipment and supplies, and other operational indicators were added to the system during various modifications. Information from the DDC was used to inform the COVID-19 response and operations at national and local levels and facilitated research at academic and nongovernmental agencies. The development of the DDC system demonstrates that an effective surveillance system for use by all health-care facilities is achievable through strong national leadership, the use of available technology and adaptive information systems, and the establishment of networks across different health facilities and stakeholders.